Nature Methods Techniques for life scientists and chemists - De Souza, Natalie; SpringerLink (Online service) (New York : Nature Publishing Group US : Imprint: Nature Research.)
Nature Methods offers a unique interdisciplinary forum for the publication of novel methods. Nature Methods focuses on the life sciences, combining practical, technique-driven subject matter with rigorous peer-review standards to ensure that readers are consistently presented with only the most valuable and highest quality methodological research. The journal offers its readers primary research papers as well as an array of opinions, reviews and short journalistic pieces to provide busy researchers with a broad, yet easily absorbed perspective of important methodological developments in the life sciences.
Keywords: Biomedical engineering; Life sciences; Proteomics; Bioinformatics; Microscopy; Biology -- Technique; Life Sciences, general; Biological Techniques; Biological Microscopy; Biomedical Engineering/Biotechnology.; Bioinformatics; Proteomics